Studi Fenomenologi Pengalaman Orang Hiv/Aids (Odha) Dalam Mendapatkan Dukungan Keluarga di Yayasan Lantera Minangkabau Support Padang: Phenomenological Study of the Experience of People with HIV/Aids (Odha) in Getting Family Support at Yayasan Lantera Minangkabau Support Padang - Reni Prima Gusty; Mutia Farlina; Alfitri (NERS Jurnal Keperawatan, 2015)
Be the people living with HIV as heavy thing in life, to confront these conditions people living withHIV desperately need family support as main support to overcome various problems that appear about theircondition such as complex diseases, psychological distress, stigma and discrimination.. But not all the PLWHAget support they need. The purpose of this research is to exploration, understand and describe the experience ofPLWH get family support. Qualitative design research with approach of descriptive Phenomenology. Datacollection with the interview on 5 participants in the Yayasan Lantera Minangkabau. Data analysis using theCollaizi technique. The research found seven themes, PLWHA has rejected response the diagnosis of HIV/AIDSand received response the diagnosis of HIV/AIDS. The family has rejected response when known the familymembers diagnosed of HIV/AIDS and received response the diagnosis of HIV/AIDS. Family support they need,family support they received and family support they received as they need. Family support they need such asemotional support, instrumental support, and informational support. The most family support wich need ofPLWHA is emotional support such as attention, support, affection and peace. Four participants has been gettingfamily support they need and one participant yet optimized family support he need,,it cause participant notready to tell another family about HIV status related the factors of risk and condition of family health. Based onthe themes expected for family to provide support that is full of empathy, received and understanding theconditions of PLWHA and get right information about HIV/AIDS.